Baula ; Postal service Mga kuwento ng Apo - Lazaro, Cheche (Quezon City Probe Productions, 1988)
Col. Francisco Baula, Jr., an AFP soldier who is confined to the stockade, is killed by Stockade guards, allegedly for trying to escape. Looks at the complaints about the postal service in the Philippines. The Apo Hiking Society, the singing trio talks about their songs, philosophers and concerns.
Paula (21 min.) -- Postal Service (13 min.) -- Mga Kuwento ng Apo (14 min.)
VHS.
Keywords: Baula, Francisco; Apo Hiking Society; Postal service -- Philippines